Tourism Attractiveness: Main Components for a Spacial Appraisal of Major Destinations According with Ecosystem Services Approach - Pilogallo, Angela; Saganeiti, Lucia; Scorza, Francesco; Las Casas, Giuseppe (Computational Science and Its Applications - ICCSA 2018, 2018)
It is widely recognized that tourism sector plays an important role in territorial analysis both because of its economic and employment potential and its environmental and social implications. Investigating dynamics that influence tourist attractiveness and receptivity is fundamental in territorial planning sector in order to monitor regional and sustainable development policies, above all with a view to pursuing the 17 Sustainable Development Goals (SDGs) defined by the 2030 Agenda for Sustainable Development [1]. Within the methodological framework established by the Millenium Ecosystem Assessment [2], the evaluation of tourism specialization degree was carried out following the ecosystem services approach and relying on inVEST, a spatially-explicit model developed with the aim of providing a decision support system able to quantify the set of goods and services profitable for human well-being and provided by ecosystems. The study area, located in the Southern Italy and including regional territories of Basilicata and Puglia regions, was chosen because in recent years it has been characterized by a steadily growing flow of arrivals and presence which a significant impetus was given by the designation of Matera as the Capital of European Culture for 2019. The work is completed by the contextualization of the results obtained within the framework of tourist attractiveness and accessibility of the examined area, which presents strong differences as much as it includes Basilicata, a region poorly infrastructuralized and only recently emerging in the tourism market, and Puglia considered instead a very sought-after Italian destinations.